Consumer Responces to CSR in Greek Banking Sector: Does CSR Really Matter? - Panagiota Xanthopoulou; Sahinidis Alexandros; Stremmenou Katerina (European Scientific Journal, ESJ, 2022)
This paper focuses on investigating the impact of Corporate Social Responsibility on consumers’ preferences and loyalty in the banking sector. The researchers examined the main concepts associated with CSR and how it is related with the choice and the retention of customers to a specific bank. 67 individuals participated in a qualitative research, which was conducted through semi-structured interviews. The purpose of the research was to analyze the extent to which CSR actions affect customers’ choice and loyalty to a bank. The main conclusions that emerged reveal that although the satisfaction and commitment, as well as the positive perception of consumers depends on the trust created by the banks, customers in Greece still believe that the CSR actions implemented by banks only contribute to increasing their organizational profits through the improved corporate reputation and recognition. It is thus evident that CSR does not have a significant impact on customers’ attraction and loyalty. This paper also identified that one of the major problems in the banking sector is the lack of public confidence in the way banks operate and the special role they play in modern societies.